The impact of commercial hunting tourism on the financial autonomy of rural territorial communities in the context of post-war recovery - Kornia, Veronika (Актуальні питання економічних наук, 2026)
Current challenges in the socio-economic development of rural territorial communities, driven by the consequences of military actions, necessitate the search for effective mechanisms for generating local revenues based on the use of natural resource potential. Particular importance is attached to integrating hunting management into the tourism sector as a tool for diversifying economic activity and enhancing the financial capacity of territories. The purpose of the study is to determine the role of commercially oriented use of hunting resources in generating income and ensuring the financial sustainability of rural territorial communities in the context of post-war recovery. The methodological basis of the study includes methods of system analysis, comparison, generalization, structural-logical and statistical analysis, which enabled the assessment of the resource, institutional, and economic components of hunting management, as well as the identification of the relationship between tourism activity and the financial performance of territories. The study results indicate that the existing resource base of hunting grounds, combined with a stable institutional structure, creates preconditions for the development of specialized tourism products. Regional differentiation in the efficiency of potential utilization has been identified, determined by the level of infrastructure development, security conditions, and the degree of integration into the tourism market. It is substantiated that transforming hunting activities into a comprehensive service product ensures the formation of a multi-channel income system, generates a multiplier effect on the local economy, and contributes to strengthening the financial autonomy of communities. A phased approach to the development of this sector is proposed, covering institutional, infrastructural, service, and marketing components. The practical significance lies in the possibility of applying the proposed approach and analytical results by local self-government bodies to develop effective territorial development strategies, expand revenue sources, and strengthen the financial sustainability of rural territorial communities.